2011
DOI: 10.1055/s-0031-1285873
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Wall Reconstruction for Primary Malignancies in Children: Short- and Long-term Results

Abstract: Surgical reconstruction after resection of malignant thoracic wall tumors using non-rigid prosthetic material is safe and effective in pediatric patients, whereas rigid prosthetic material might dislocate. Scoliosis represents a long-term complication after chest wall reconstruction and should be monitored during routine follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 17 publications
1
28
0
6
Order By: Relevance
“…Sabanathan et al 27 and Saenz et al 28 affirm the need for total resection of the affected rib together with the ribs immediately above and below in order to achieve a wide resection. Total rib resections are often associated with scoliosis 29,30 and reduction of lung function, 31 which is in accordance with our findings. Hayes et al 32 claim that only the involved ribs need to be resected, with Rao et al 33 and, more recently, Meys et al 34 drawing the same conclusions.…”
Section: Special Aspects Of Surgical Therapysupporting
confidence: 92%
“…Sabanathan et al 27 and Saenz et al 28 affirm the need for total resection of the affected rib together with the ribs immediately above and below in order to achieve a wide resection. Total rib resections are often associated with scoliosis 29,30 and reduction of lung function, 31 which is in accordance with our findings. Hayes et al 32 claim that only the involved ribs need to be resected, with Rao et al 33 and, more recently, Meys et al 34 drawing the same conclusions.…”
Section: Special Aspects Of Surgical Therapysupporting
confidence: 92%
“…A 2006 report by Soyer et al [3] described 1 case of clinically significant scoliosis in a child undergoing primary tissue repair among 17 chest wall reconstructions performed using either primary repair, or Goretex, Dura, or Neuropatch prosthetics. Dingemann et al [4] followed with a report in 2011 of 8 patients undergoing reconstruction using synthetic mesh with or without titanium bar implantation for additional stabilization. Zero of the 8 patients developed clinically significant scoliosis using the diagnostic criteria applied to our series.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, both tissue repair and synthetic mesh reconstruction have resulted in significant rates of progressive scoliosis and/or restrictive lung disease [1,2]. Contemporary case series describe improved results with new prosthetic materials and techniques, but the placement of permanent foreign bodies in children remains a concern [3,4].…”
mentioning
confidence: 99%
“…The authors concluded that Surgisis is a preferable mesh option for chest wall reconstruction in children because they observed mesh constriction and the requirement for its removal owing to infection while they were using Goretex [3]. One recent case series reported their results of chest wall reconstruction owing to malignancy in 8 patients with a mean age of 10.6 years (range, 4.1-18.9 years) [18]. They found that the use of expanded Goretex soft tissue patches, absorbable Vicryl patches, and xenograft Tutopatch was safe and effective, but stabilization using titanium bars could be complicated by dislocation and require removal [18].…”
Section: Discussionmentioning
confidence: 99%
“…One recent case series reported their results of chest wall reconstruction owing to malignancy in 8 patients with a mean age of 10.6 years (range, 4.1-18.9 years) [18]. They found that the use of expanded Goretex soft tissue patches, absorbable Vicryl patches, and xenograft Tutopatch was safe and effective, but stabilization using titanium bars could be complicated by dislocation and require removal [18]. This is contradictory to the report by Smith and Campbell [3] that suggested the safety of titanium bars.…”
Section: Discussionmentioning
confidence: 99%